From Platon to Paltrow: knowledge and care of the self in the 21st century - Guzmán Ferreto, Irene (2017)
Classical Era philosophers reflected on multiple times on the knowledge and care of the self, as basic conditions for leading a good life. This article questions the validity of such concepts in the present time, while pondering what defines a good life in the 21st century. To achieve this, the article analyzes the role of celebrities, and the power these people wield as influencers over their followers’ behaviors. Gwyneth Paltrow and her lifestyle site Goop are observed as a paradigmatic case. Cases like this one allow us to depict a way of caring for oneself that is concerned about the practices, but not about the knowledge of the self.